2010
DOI: 10.1186/1471-213x-10-93
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-25 has a functional role in mouse secondary palate development and is a downstream target of TGF-β3

Abstract: BackgroundDevelopment of the secondary palate (SP) is a complex event and abnormalities during SP development can lead to cleft palate, one of the most common birth disorders. Matrix metalloproteinases (MMPs) are required for proper SP development, although a functional role for any one MMP in SP development remains unknown. MMP-25 may have a functional role in SP formation as genetic scans of the DNA of human cleft palate patients indicate a common mutation at a region upstream of the MMP-25 gene. We report o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 29 publications
0
21
0
1
Order By: Relevance
“…This result lends support to the Western blot findings, since it is known that excess TGF-β3 leads to increased pSmad1 expression. [12] However, secreted TGF-β1, TGF-β2, and BMP-4 were not different between groups (p > 0.05, data not shown). The possibility that the secreted TGF-β3 could potentiate an auto-feedback loop on the CAH-X fibroblasts was tested; however, no effect was seen in the fibroblasts (data not shown).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…This result lends support to the Western blot findings, since it is known that excess TGF-β3 leads to increased pSmad1 expression. [12] However, secreted TGF-β1, TGF-β2, and BMP-4 were not different between groups (p > 0.05, data not shown). The possibility that the secreted TGF-β3 could potentiate an auto-feedback loop on the CAH-X fibroblasts was tested; however, no effect was seen in the fibroblasts (data not shown).…”
Section: Resultsmentioning
confidence: 89%
“…[18] In mouse models of cleft palate, it was shown that increased TGF-β3 in tissue and palatal fibroblasts led to increased signaling of pSmad1 and MMP-25 and MMP-13 (collagenase-3), which are also important in palate formation. [12, 13]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable biological evidence implicates MMPs as key molecules during palatogenesis for their role in extracellular matrix remodeling (Morris-Wiman et al, 2000; Blavier et al, 2001; Brown et al, 2002; Brown and Nazarali, 2010; de Oliveira Demarchi et al, 2010). In this study, we investigated 45 polymorphisms in 14 MMP and TIMP genes relevant for craniofacial development as candidates for oral clefts in a large case-control dataset from Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-25 gene expression is high during the development of mouse secondary palate, wherefore MMP-25 is the only MMP showing a functional role (Brown and Nazarali, 2010).…”
Section: Mt6-mmp (Mmp-25)mentioning
confidence: 99%